I Prefer to be Old School and Safe”: Fear of Fraud and Governance of Risk in Nigeria’s Cashless Ecosystem (2023)
This article provides insight into the prevalence of fraud in Nigeria’s financial cashless ecosystem and how trust is being built in the system to check the growing menace. It is motivated by two overarching questions: Does fear of fraud constitute an impediment to financial inclusion? How does the existence or otherwise of risk governance mechanisms mediate the nexus between electronic fraud and financial inclusion? Using qualitative methods to probe participants in southwestern Nigeria on these issues, the findings show how fear of fraud, indirect experiences of fraud, and fraud governance shape adoption and behaviour in the Nigerian banking system.